BIBLICAL CHRISTIAN WORLDVIEW ON POST-HARVEST PATHOGENIC FUNGI IN THE TRADITIONAL MARKET CORN SEEDS - Christian, Grace Purnamasari; Irawati, Wahyu (JOHME: Journal of Holistic Mathematics Education, 2021)
The post-harvest fungi is one of the greatest cause of various diseases. Particularly, in fungus that infects seeds, the toxic substance called aflatoxin is found. This has caused us to wonder: Has fungi been pathogenic fungi since the beginning of creation? The purpose of this research is to study: 1) The Place of Fungi in God’s Original Creation and the Origin of Pathogenic Fungi, 2) Characterization of post-harvest fungus on corn seeds, 3) Aspergillus sp.’s Structure as Proof of God’s Wonderful Original Creation and Providence, and 4) The factors that contribute to the growth of fungi in post-harvest corn seeds and our responsibility. We conclude that in the beginning, fungi were a part of God’s originally good and perfect creation. These fungi were created by God with the structure and function to support its operation in fulfilling God’s creative purpose. The complex structure of Aspergillus niger and Aspergillus flavus that infected the corn seeds showed God’s providence after the Fall. Pathogenic fungi were the result of the Fall of man into sin. Their growth is caused by the failure to give proper care to the crops. But this should not discourage us since the Bible tells us that God is continually working to restore His creation. Therefore, we are called to be stewards of His creation, to develop and preserve whatever is entrusted in our hands, including the crops for God’s glory and under His authority until He has fully renewed and restored everything.BAHASA INDONESIA ABSTRACT: Jamur pasca panen merupakan salah satu penyebab terbesar timbulnya berbagai penyakit, khususnya disebabkan oleh jamur yang menginfeksi biji-bijian dan menghasilkan substansi beracun disebut dengan aflatoksin. Keadaan ini menimbulkan pertanyaan apakah jamur patogenik ada sejak awal penciptaan? Penelitian ini bertujuan untuk mempelajari: 1) Posisi jamur patogenik di awal penciptaan dan asal mula jamur patogenik, 2) karakteristik jamur pasca panen pada biji jagung, 3) struktur Aspergillus sp sebagai bukti dari providensi Allah akan ciptaanNya yang sangat luar biasa, 4) faktor-faktor yang berkontribusi terhadap pertumbuhan jamur pasca panen biji jagung dan Tanggung jawab kita. Dari hasil penelitian ini disimpulkan bahwa pada mulanya, jamur merupakan bagian ciptaan Allah yang sungguh amat baik dan sempurna. Struktur yang kompleks dari Aspergillus niger dan Aspergillus flavus yang menginfeksi biji jagung menunjukkan providensi Allah setelah kejatuhan dosa. Pertumbuhan jamur patogenik merupakan gambaran kejatuhan manusia ke dalam dosa yaitu kegagalan manusia untuk memberikan pemeliharaan yang memadahi pada biji-bijian pasca panen. Namun demikian, keadaan ini tidak mematahkan semangat kita karena Alkitab mengatakan bahwa Allah masih terus bekerja untuk memulihkan ciptaanNya. Oleh karena itu, diharapkan kita semua menjadi pelayan atas ciptaanNya untuk mengembangkan dan menjaga apa yang dipercayakan kepada kita di bawah otoritasNya termasuk biji-bijian untuk memuliakan Allah hingga Dia secara penuh memperbaharui dan memulihkan segala sesuatu